Comparison of Postoperative Outcomes in Standard Versus Tubeless Percutaneous Nephrolithotomy - Hasham Khan; Monib Ahmad; Ehsan-ul-Haque; Muhammad Jafar; Raza-ul-Hassan; Omer Dilawar (Pakistan Journal of Medical Research)
Objective: To compare the outcomes of tubeless percutaneous nephrolithotomy (PCNL) over standard PCNL in terms of postoperative pain and rescue analgesia needed.